The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.amjcard.2004.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rheolytic thrombectomy before direct infarct artery stenting versus direct stenting alone in patients undergoing percutaneous coronary intervention for acute myocardial infarction

Abstract: This randomized trial compared rheolytic thrombectomy before direct infarct artery stenting with direct infarct artery stenting alone in 100 patients with a first acute myocardial infarction (AMI). The primary end point of the study was early ST-segment elevation resolution, and the secondary end points were corrected Thrombolysis In Myocardial Infarction (TIMI) frame count, infarct size, and 1-month clinical outcome. The primary end point rates were 90% in the thrombectomy group and 72% in the placebo group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 11 publications
1
88
0
6
Order By: Relevance
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…208 Also, no reduction of microvascular obstruction and infarct size was found with MRI. [209][210][211] Hyperoxemia, 212,213 aspiration or mechanical thrombectomy, [214][215][216][217][218][219][220][221] and intra-aortic balloon counterpulsation 222 did not reduce infarct size or improve coronary blood flow. More recently, also the cardioprotection by cyclosporine A which had been shown in a small-scale proof-of-concept trial 223 was not confirmed in another smaller study with prethrombolytic cyclosporine A 224 and, importantly, not in 2 larger-scale phase III trials, Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients (CIRCUS) and CyclosporinE A in Reperfused Myocardial Infarct (CYCLE).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In this regard, the use of a mechanical device for thrombus removal or trapping to improve clinical outcomes after p-PCI is attractive, and the efficacy of these devices has been tested in many clinical trials. Although some data, especially those regarding the use of distal protection devices, have failed to show clinical benefits due in part to patient and device selection [48][49][50][51][52][53] , many recent large-scale randomized trials have demonstrated significant improvements in myocardial perfusion 45,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the left ventricular function 64,65) in addition to reduced mortality 68) ( 69) . In addition, Burzotta et 70) .…”
Section: Thrombus Aspiration/distal Protection Therapy and Its Efficacymentioning
confidence: 99%
“…16 Angiographically visible thrombus was required in 5 trials. 13,24,32,33,35 Patients in shock or those requiring intra-aortic balloon counterpulsation or mechanical ventilation were excluded from 11 trials, 13,15,16,18,20,24,26,29,31,34,35 and patients with previous coronary artery bypass were excluded from 9 trials. 12,14,16,18,20,24,28,34,35 Only 2 RCTs specifically excluded patients with a left ventricular ejection fraction Ͻ30%.…”
Section: Differences In Inclusion and Exclusion Criteria In Selected mentioning
confidence: 99%